Exploring community resilience: A qualitative study on earthquake preparedness and response in vulnerable regions - Jeevan Gwachha (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The way communities handle disasters directly influences earthquake impact reduction most significantly within regions that are easily damaged like Nepal. This research analyzes the subjective elements of preparedness and risk recognition and response approaches among Kathmandu-based communities. Methods: The research used questionnaire surveys to gather information from individuals representing different family sizes, methods of income and age brackets. The study analyzed several driving elements for preparedness that combine information accessibility with neighborhood safety evaluations and citizen involvement and institutional backing. Findings: The data indicates that homeowners showed mixed assessments regarding their house structural readiness for major earthquakes since 46.9% said their homes were strong enough while 50% remained unsure about it. The majority (75.8%) of the population used social media for earthquake information yet fewer than one-third (33.3%) were satisfied with training and nearly nine-tenths (87.9%) had not received preparedness materials. Studies found that an unsatisfactory pace of recovery occurred after disasters because 33.3% of communities needed help months later and 33.3% received no assistance. Community engagement together with traditional knowledge showed promise as potential resilience-builders yet formal disaster planning systems demonstrate minimal integration of these approaches. Conclusion: Research suggests the augmentation of educational campaigns about disasters should be paired with better warning alerts together with financial help for building improvements and more organized institutional cooperation. The establishment of comprehensive measures to bridge these areas will help Nepal construct resilient communities. Novelty/originality of this article: The research adds important knowledge to earthquake risk reduction science along with community resilience approaches that benefits policymakers through their work with disaster management agencies.